2098. Cytomegalovirus (CMV) Infection Following Hematopoietic Cell Transplantation (HCT) with Post-transplant Cyclophosphamide (PTCy): Outcomes in Haploidentical versus Matched or Mismatched Unrelated Donor (MUD/MMURD) Allografts. (15th December 2022) - Little, Jessica S; Ni, Jian; Shapiro, Roman M; Romee, Rizwan; Soiffer, Robert J; Sherman, Amy C; Ho, Vincent T T; Issa, Nicolas C
Abstract: Background: PTCy is increasingly being used in MUD/MMURD, and haploidentical donor HCT for prevention of graft-versus-host disease (GVHD). PTCy has been associated with increased risk of infections including CMV viremia after HCT. It remains unclear if this observation is independent of graft type. This study aims to evaluate the incidence of clinically significant CMV infection (CS-CMVi) following PTCy in MUD/MMURD compared to haploidentical donor HCT. Methods: We performed a single-center retrospective study of all adults undergoing HCT with PTCy between January 1, 2015 and July 1, 2021. CS-CMVi, defined as CMV viremia or disease requiring initiation of CMV therapy, was evaluated in two groups: haploidentical HCT (n=170) and MUD/MMURD HCT (n=137). We assessed the incidence of CMV viremia, CS-CMVi, and CMV disease, as well as incidence of letermovir breakthrough infections and late CMV events after cessation of prophylaxis. Cumulative Incidence Functions were calculated based on time to CS-CMVi using dates of infection-free death, disease relapse, and repeat HCT as competing risks. Results: The one-year cumulative incidence of CS-CMVi accounting for competing risks was 25% (95% CI 19 – 32) in the haploidentical group and 18% (95% CI 12 – 25) in the MUD/MMURD group (HR 1.50; 95% CI 0.91 – 2.46; p=0.11). CMV disease was rare, (haploidentical n=1; MUD/MMURD n=1) and no patients died of CMV infection. CS-CMVi in CMV seropositive patients was more common in the haploidentical group (23% versus 9%; p=0.002). Notably, CMV D+/R- HCT patients had a significantly higher rate of CS-CMVi in the MUD/MMURD cohort than in the haploidentical cohort. Of the CS-CMVi, letermovir breakthrough constituted 26% in the haploidentical group and 29% in the MUD/MMURD group. Late infections after cessation of letermovir occurred in only 14% of cases in the haploidentical group and 25% of cases in the MUD/MMURD group. Conclusion: Rates of CS-CMVi, CMV viremia, and CMV disease were similar following PTCy in haploidentical donor HCT and MUD/MMURD HCT. CS-CMVi in CMV seropositive patients was more common in the haploidentical donor HCT population and MUD/MMURD HCT recipients had a higher incidence of CS-CMVi in the D+/R- patients. Disclosures: Roman M. Shapiro, M.D., Miltenyi Biotec: Honoraria Rizwan Romee, M.D., Crispr Therapeutics: Grant/Research Support|Glycostem Therapeutics: Advisor/Consultant|NK Therapeutics: Advisor/Consultant|Skyline Therapeutics: Grant/Research Support Robert J. Soiffer, M.D., CSL Behring: Advisor/Consultant|Gilead: Career Chair Development Award|Jasper Therapeutics: Advisor/Consultant|Jazz Pharmaceuticals: Advisor/Consultant|Juno (BMS): DSMB|Kiadis: Board Member|Vor: Advisor/Consultant Vincent T. T. Ho, M.D., Alexion Pharmaceuticals: Advisor/Consultant|Allovir: Advisor/Consultant|Allovir: DSMC|Jazz Pharmaceuticals: Grant/Research Support|Omeros: Advisor/Consultant Nicolas C. Issa, MD, AiCuris: Grant/Research Support|Merck: Grant/Research Support.